The Influence of Service Quality on Customer Satisfaction and Customer Loyalty at Richeese Factory in Denpasar City : (Case Study at PT. Richeese Kuliner Indonesia) - Silva, Avelar Imanuel Natalicio Da Conceicao E; Junaedi, I Wayan Ruspendi; Utama, I Gusti Bagus Rai; Trimuti, Christimulia Purnama (The Eastasouth Management and Business, 2024)
Richeese Factory must execute the most effective marketing mix to advance its business, necessitating a thorough study and analysis of its marketing methods for fast food restaurants. This analysis will enable Richeese Factory to sustain and enhance its operations. This study aims to assess the impact of tangible evidence, dependability, responsiveness, assurance, and empathy on customer satisfaction and loyalty. To assess the impact of customer satisfaction on customer loyalty at Richeese Factory in Denpasar City. This study employs a quantitative research methodology. The research sample comprised 195 customers of Richeese Factory Denpasar. Methods of data collecting employing questionnaires. Analytical methodologies employing Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings indicated that Physical Evidence, Reliability, and Assurance significantly influence Customer Satisfaction, however Responsiveness and Attention do not have a substantial impact on Customer Satisfaction. Physical Evidence, Responsiveness, and Attention significantly influence Customer Loyalty; however, Reliability and Assurance do not have a major impact on Customer Loyalty. Customer satisfaction significantly influences customer loyalty. Richeese Factory Denpasar City is advised to prioritize Customer Satisfaction by periodically assessing the quality of service and food and beverage offerings supplied to patrons.